2020
DOI: 10.1155/2020/4717258
|View full text |Cite
|
Sign up to set email alerts
|

Ezetimibe Attenuates Oxidative Stress and Neuroinflammation via the AMPK/Nrf2/TXNIP Pathway after MCAO in Rats

Abstract: Oxidative stress and neuroinflammation play essential roles in ischemic stroke-induced brain injury. Previous studies have reported that Ezetimibe (Eze) exerts antioxidative stress and anti-inflammatory properties in hepatocytes. In the present study, we investigated the effects of Eze on oxidative stress and neuroinflammation in a rat middle cerebral artery occlusion (MCAO) model. One hundred and ninety-eight male Sprague-Dawley rats were used. Animals assigned to MCAO were given either Eze or its control. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(66 citation statements)
references
References 55 publications
1
60
0
Order By: Relevance
“…Beyond its powerful cholesterol lowering effects, the latest evidence shows that Ezetimibe has additional pleiotropic effects. In fact, Ezetimibe has been demonstrated to reduce oxidative stress through the activation of the AMP-activated protein kinase (AMPK)/Nrf2 pathway in animal models of nonalcoholic steatohepatitis [22] and ischemic stroke [23,24]. Furthermore, there are data showing that Ezetimibe can reduce the expression of ER stress markers in liver extracts of Zucker obese fatty rats [25] and that Ezetimibe may increase the glutathione content in rat livers subjected to IR [26].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond its powerful cholesterol lowering effects, the latest evidence shows that Ezetimibe has additional pleiotropic effects. In fact, Ezetimibe has been demonstrated to reduce oxidative stress through the activation of the AMP-activated protein kinase (AMPK)/Nrf2 pathway in animal models of nonalcoholic steatohepatitis [22] and ischemic stroke [23,24]. Furthermore, there are data showing that Ezetimibe can reduce the expression of ER stress markers in liver extracts of Zucker obese fatty rats [25] and that Ezetimibe may increase the glutathione content in rat livers subjected to IR [26].…”
Section: Introductionmentioning
confidence: 99%
“…Adiponectin (APN) was found to reduce oxidative stress and NLRP3 inflammasome activation after cerebral ischemia-reperfusion injury by regulating AMPK/GSK-3 ( Liu et al, 2020 ). Additionally, Yu J et al also found that Ezetimibe (Eze) reduces oxidative stress and subsequent neuroinflammatory response by activating AMPK/Nrf2/TXNIP pathways in MCAO rats ( Yu et al, 2020 ). These findings manifest that AMPK activation plays a protective role in ischemic brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the deletion of endothelial TXNIP in mice or in vivo anti-TXNIP treatment protects from oxidative stress and NLRP3 inflammasome activation [ 13 , 21 ]. Metformin or other compounds are also used to lower TXNIP aortic levels in vivo or endothelial levels in vitro in order to restrain NLRP3 activation and protect from endothelial dysfunction and cardiovascular risk factors [ 60 , 67 , 87 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 ]. The regulation of the NLRP3 inflammasome by the TRX-TXNIP complex is believed to be controlled by Nrf2 and AMPK [ 60 , 102 , 103 , 104 , 106 , 107 ].…”
Section: Txnip Is a Multifunctional Proteinmentioning
confidence: 99%
“…Metformin or other compounds are also used to lower TXNIP aortic levels in vivo or endothelial levels in vitro in order to restrain NLRP3 activation and protect from endothelial dysfunction and cardiovascular risk factors [ 60 , 67 , 87 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 ]. The regulation of the NLRP3 inflammasome by the TRX-TXNIP complex is believed to be controlled by Nrf2 and AMPK [ 60 , 102 , 103 , 104 , 106 , 107 ]. The overexpression of TXNIP activates the TLR4-NF-κB-NLRP3 inflammasome signaling pathway with increased MyD88, NLPR3 inflammasome, and ASC expression, as well as the increased phosphorylation of lκBα and p65, thus promoting downstream NF-κB activation [ 109 ].…”
Section: Txnip Is a Multifunctional Proteinmentioning
confidence: 99%